(untitled) - Pratt, William K. (Hoboken, N.J., 2007)
The Fourth Edition of Digital Image Processing provides a complete introduction to the field and includes new information that updates the state of the art. The text offers coverage of new topics and includes interactive computer display imaging examples and computer programming exercises that illustrate the theoretical content of the book. These exercises can be implemented using the Programmer's Imaging Kernel System (PIKS) application program interface included on the accompanying CD
Keywords: Image processing,Tạo hình ảnh; Digital techniques,Kỹ thuật số